Proteomic Reveals Reasons for Acquired Drug Resistance in Lung Cancer Derived Brain Metastasis Based on a Newly Established Multi-Organ Microfluidic Chip Model - Xu, Mingxin; Wang, Yingyan; Duan, Wenzhe; Xia, Shengkai; Wei, Song; Liu, Wenwen; Wang, Qi (Frontiers in Bioengineering and Biotechnology, 2020)
Anti-tumor drugs can effectively shrink the lesions of primary lung cancer; however, it has limited therapeutic effect on patients with brain metastasis (BM). A BM preclinical model based on a multi-organ microfluidic chip has been established proficiently in our previous work. In this study, the BM subpopulation (PC9-Br) derived from the parental PC9 cell line was isolated from the chip model and found to develop obvious resistance to antineoplastic drugs including chemotherapeutic agents (cisplatin, carboplatin, pemetrexed) and tyrosine kinase inhibitors (TKIs) which target epidermal growth factor receptor (EGFR); this suggested that the acquisition of drug-resistance by brain metastatic cells was attributable to the intrinsic changes in PC9-Br. Hence, we performed proteomic and revealed a greatly altered spectrum of BM protein expression compared with primary lung cancer cells. We identified the hyperactive glutathione (GSH) metabolism pathway with the overexpression of various GSH metabolism-related enzymes (GPX4, RRM2, GCLC, GPX1, GSTM4, GSTM1). Aldehyde dehydrogenases (ALDH1A1, ALDH3A1) were also found to be upregulated in BM. What’s more, loss of EGFR and phosphorylated EGFR in PC9-Br gave reasons for the TKIs resistance. Collectively, our findings indicated potential mechanisms for the acquirement of drug resistance occurred in BM, providing new strategies to overcome therapeutic resistance in lung cancer BM.